The use of managerial tools in third sector management: relevance of BSC application - Ensslin, Leonardo; Vianna, William Barbosa (Revista Gestão da Produção Operações e Sistemas, 2007)
The academic discussions on management in the Third Sector in Brazil are incipient. They hold the paradox related to the management of organizations that, even without presenting profit, are regarded as organizations, as well as the issue on the use of inadequate management tools xx that assist xx profit organizations with predominant economic and financial interest with regard to organizations with diversified natures and purposes, both from the market and the governments. The Balanced Scorecard (BSC) is a tool which allows for the alignment of strategic performance of the third sector institution within its society perspectives, its internal processes, learning and growth. The strategic map and the detailing of the BSC panel – as well as of the strategic theme on the learning and growth – are presented in this paper, confirming that the BSC methodology has a strong relevance in a third sector organization, when adequately adapted. Such fact is confirmed in this case study, applied to the Salesian Body of Social Action located in the city of Porto Alegre, state of Rio Grande do Sul, Brazil. xx The strategic theme of the organizational learning was underscored, especially for the organizations involved with intangible assets, focusing on the development of the individual skills of the collaborators and on the commitment of the social responsibility. Keywords: Third sector organizations; Balanced Scorecard; Strategy implementation.